Penerapan Strategi Value For Money (3E) dalam Meningkatkan Kinerja Pemerintah Daerah Kota Jakarta Tahun 2022 - Zanneta Althaf Nabila; Sonny Fransisco Siboro; Tasya Derdameisya Aurelia; Mochamad Fachrizal Yusuf (Pusat Riset dan Inovasi Nasional, 2024)
This study explores the use of Value for Money (VFM) strategies to improve local government performance of Jakarta City in 2022. Using qualitative research methods, datal was collectedl through lin-depthl interviews andl document analysis. Thel results show thatl VFM has improved local government performance in managing budgets and resources, enabling better service provision to residents. The findings highlight the importance of efficiency, effectiveness and accountability in public financial management, and emphasize the potential of VFM strategies to improve public sector performance.